2022
DOI: 10.1021/acs.jpcc.2c01721
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles for the Development of Gd(III) Polarizing Agents for Magic Angle Spinning Dynamic Nuclear Polarization

Abstract: Nuclear magnetic resonance suffers from an intrinsically low sensitivity, which can be overcome by dynamic nuclear polarization (DNP). Gd(III) complexes are attractive exogenous polarizing agents for magic angle spinning (MAS) DNP due to their high chemical stability in contrast to nitroxide-based radicals. However, even the state-of-the-art Gd(III) complexes have so far provided relatively low DNP signal enhancements of ca. 36 in comparison to standard DNP biradicals, which show enhancements of over 200. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…It was concluded that signal enhancements from gadolinium PAs are inversely proportional to D 2 , and so a lower value of D leads to larger NMR signal enhancements, as powerfully demonstrated from the synthetic design of the structural complex [Gd­(tpcatcn)] . The value of D measured and the enhancement factors ϵ obtained in this work compare favorably with those of Gd­(tpcatcn), [Gd­(dota)­(H 2 O)] − , and GdCl 3 , from the previous literature , and the empirical reciprocal quadratic relationship . The value of D for the ZFS obtained from the EPR spectrum of GdCl 3 ·6H 2 O is marginally smaller (by a factor of ∼1.14) than the D reported in this work for the ZFS of Gd­(NO 3 ) 3 ·6H 2 O.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…It was concluded that signal enhancements from gadolinium PAs are inversely proportional to D 2 , and so a lower value of D leads to larger NMR signal enhancements, as powerfully demonstrated from the synthetic design of the structural complex [Gd­(tpcatcn)] . The value of D measured and the enhancement factors ϵ obtained in this work compare favorably with those of Gd­(tpcatcn), [Gd­(dota)­(H 2 O)] − , and GdCl 3 , from the previous literature , and the empirical reciprocal quadratic relationship . The value of D for the ZFS obtained from the EPR spectrum of GdCl 3 ·6H 2 O is marginally smaller (by a factor of ∼1.14) than the D reported in this work for the ZFS of Gd­(NO 3 ) 3 ·6H 2 O.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, several gadolinium-based PAs have been developed for MAS DNP NMR experiments with a specific set of design principles in mind. 44 It was concluded that signal enhancements from gadolinium PAs are inversely proportional to D 2 , and so a lower value of D leads to larger NMR signal enhancements, as powerfully demonstrated from the synthetic design of the structural complex [Gd(tpcatcn)]. 43 The value of D measured and the enhancement factors ϵ obtained in this work compare favorably with those of Gd(tpcatcn), [Gd(dota)(H 2 O)] − , and GdCl 3 , from the previous literature 41 , 43 and the empirical reciprocal quadratic relationship.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations